Knowledge, attitude, and practice of Gum Arabic among Malaysian users / Aimi Syifaa’ Abdul Halim - Abdul Halim, Aimi Syifaa’ (2021)
The dietary supplement has been a long-debated topic with a diverse range of opinions and viewpoints. In the case of Gum Arabic (GA), variation in the terms being used and inconsistent product information have led to confusion and impacts on the users’ practice. Past studies on GA have been focusing on clinical testing and functional properties, thereby causing inadequate investigations on users’ practice of GA. Hence, this study adopted the Knowledge, Attitude, and Practice (KAP) model to examine the relationships between knowledge, attitude, and practice of GA among users in Malaysia. Knowledge is represented separately as objective knowledge (OK), which refers to what is actually known, and subjective knowledge (SK), which refers to what people think they know. Previous research has found that both variables affected attitude and practice differently. Specifically, OK and SK were integrated into the knowledge domain of the KAP model in this study, while validated online questionnaires comprising 33 items were distributed purposively to Malaysian GA users via Facebook and WhatsApp applications. A total of 301 data were collected and analysed using IBM SPSS Statistics version 26.0 software and the Smart-PLS 3.0 software was also used to examine the relationships between the variables. The validity of the measurement model is satisfactory, and the findings supported several hypothesised relationships proposed through path analysis using PLS-SEM. The findings provide evidence that OK has a positive and significant relationship with practice (p < 0.05), whereas SK greatly acts as a major predictor in its relationship with attitude (p < 0.01). The findings also revealed a positive and significant relationship between attitude and practice (p < 0.01), while attitude was found to mediate the relationship between SK and practice (p < 0.01). These findings make a noteworthy contribution to the body of knowledge, especially in explaining the behavior of GA users. In terms of practical contribution, this study offers valuable insights for the users, authorities, producers, and intermediaries to better understand KAP and the need for correct, reliable, and justified information that may affect users’ attitudes and practices of GA.